An investigation on sustainable supply chain management challenges for Indian thermal power plants. Issue 2 (21st September 2020) - Satapathy, Suchismita
The coal option for power generation has to play most important role in the Indian power sector for long times to come. Though it is most obvious and viable option, it comes with some salient issues like coal quality, import tie ups, mining, transport and port infrastructure, etc. which need to be analysed and addressed with long-term perspective. A low-quality, high-ash coal also creates problems for power stations, including erosion in parts and materials, difficulty in pulverisation, poor emissivity and flame temperature, low radiative transfer, and excessive amounts of fly ash containing large amounts of unburned carbons. The awareness against the environmental pollution and clean energy is increasing all over the world. As the thermal power sector is blamed for creating environmental pollution, so they are more focused on sustainability issues and subsequently trying to develop a sustainable supply chain strategy to carry out their business.